Neutrophil Evolution and Their Diseases in Humans - Leiding, Jennifer W. (Frontiers in Immunology, 2017)
Granulocytes have been preserved and have evolved across species, developing into cells that provide one of the first lines of host defense against pathogens. In humans, neutrophils are involved in early recognition and killing of infectious pathogens. Disruption in neutrophil production, emigration, chemotaxis, and function cause a spectrum of primary immune defects characterized by host susceptibility to invasive infections.